Once in a blue moon: A rare case of Duchenne muscular dystrophy complicated by COVID-19 - Kukreja, Amodini; Kalvapudi, Devaki; GV, Chaithra; Arunachala, Sumalatha (Indian Journal of Case Reports, 2022)
Patients suffering from Duchenne Muscular Dystrophy (DMD) are at higher risk of suffering significant morbidity resulting from COVID-19, considering their pre-existing respiratory insufficiency and immunocompromised state. We present such a case who was admitted to our intensive care unit. A 21-year-old patient, who was a diagnosed case of DMD since the age of 8 and on treatment with steroids, angiotensin-converting enzyme inhibitors, and intermittent home-oxygen support, presented with fever and breathlessness and was diagnosed to have COVID-19 pneumonia. Oxygen support was provided by non-invasive ventilation (NIV), along with therapeutic and supportive treatment, namely, azithromycin, remdesivir, dexamethasone, and heparin. Dyselectrolytemia was corrected and convalescent plasma was transfused. The patient was weaned off NIV and discharged on significant improvement in his general condition. Although the treatment of COVID-19 using convalescent plasma has now fallen out of favor, we found some clinical improvement in our patient. DMD complicated by COVID-19 can seem like a daunting challenge, but providing fundamental, yet, simple treatment measures goes a long way in the patient care.